Surface Complexation Models of Pertechnetate on Biochar/Montmorillonite Composite—Batch and Dynamic Sorption Study - Daňo, Martin; Viglašová, Eva; Galamboš, Michal; Štamberg, Karel; Kujan, Jan (Materials, 2020)
The study summarizes the results of monitoring the properties of two types of sorbents, BC1 (biochar sample 1) and BC2a (biochar sample 2), prepared by pyrolysis of bamboo biomass (BC1) and as its composite with montmorillonite K10 (BC2a). The main goal was to study their applicability to the Tc (VII) separation from liquid wastes, using NH4ReO4 as a carrier. The research was focused on determining the sorbents surface properties (by XRF (X-ray fluorescence) method and potentiometric titration in order to determine the properties of surface groups—Chemical Equilibrium Model (CEM) and Ion Exchange Model (IExM) models were applied here). As well as monitoring Tc (VII) (+Re(VII)) sorption, especially to determine equilibrium isotherm, the influence of pH and kinetics. The subject of research was also the dynamics of sorption, including its mathematical–physical modeling. Both sorbents have good properties against Tc (VII), however BC2a, due to the presence of montmorillonite, is more advantageous in this respect. It has a higher sorption capacity and faster kinetic investigation. An important finding is that the optimal pH is 2–3, which is related not only to the protonation of surface groups (they have a positive charge), but also to the negative form of the existence of Tc (VII) and Re (VII): TcO4− and ReO4−.